Exogenous T3 Elicits Long Day–Like Alterations in Testis Size and the RFamides Kisspeptin and Gonadotropin-Inhibitory Hormone in Short-Day Siberian Hamsters. (June 2013) - Henson, Jerad R.; Carter, Sara N.; Freeman, David A.
Siberian hamsters ( Phodopus sungorus ) exhibit robust seasonal rhythms of reproduction driven by changes in day length. Day length is encoded endogenously by the duration of nocturnal melatonin (Mel) secretion from the pineal gland. Short duration Mel signals stimulate whereas long duration Mel signals inhibit reproduction. The mechanism by which Mel regulates the reproductive axis has not been fully characterized. In Siberian hamsters, the thyroid hormone triiodothyronine (T3 ) is thought to be part of the photoperiodic mechanism. The availability of T3 is decreased in hamsters housed in short day lengths, and injections of exogenous T3 stimulate testicular growth in short-day (SD) Siberian hamsters. Thus, T3 acts as a neuroendocrine intermediate between the Mel rhythm and the reproductive axis. The RFamides kisspeptin (Kiss1) and gonadotropin-inhibitory hormone (GnIH) also act as a link between the Mel rhythm and the reproductive axis. Expression of both of these neuropeptides is regulated by photoperiod and Mel. Kiss1 stimulates, and GnIH inhibits, the reproductive axis in long-day housed hamsters. It remains unknown whether T3 acts through changes in RFamide expression in the regulation of reproduction or whether these molecules act independently of one another. We tested the hypothesis that exogenous T3 administered to SD hamsters, a treatment that stimulates testicular growth, would also result in alterations in the patterns of Kiss1- and GnIH-immunoreactivity. Administration of T3 to SD hamsters resulted in significant testicular growth as well as a long day–like pattern of RFamide peptide expression. Thus, exogenous T3 elicited increased numbers of Kiss1-positive cells in the hypothalamic anteroventral periventricular nucleus, decreased numbers of Kiss1-positive cells in the arcuate nucleus, and a greater number of GnIH-positive cells in the dorsomedial hypothalamus compared with SD controls. The results are consistent with the hypothesis that T3 elicits alterations in the reproductive axis through alterations in RFamide peptide expression.